JURIDICAL REVIEW OF CRIMINAL ACTS INTERNET BASED SCAM (Studi Kasus Putusan PN Surabaya Nomor.1791/Pid.Sus/2019/PN.Sby) - Al Fanni, Devita Dyah; Budiastuti, Shinta Rukmi; Aryani, Esti (Wacana Hukum, 2021)
Crime in cyberspace knows no boundaries and time so that the handling is differentÂ from ordinary conventional crimes one Cybercrime crime is carding crime. This crime canbeÂ calledalsoÂ asÂ aÂ creditÂ cardwiretapÂ whichÂ isÂ classifiedÂ asÂ aÂ moderncrime. Â ThisÂ studyÂ aimsÂ toÂ examineÂ theÂ formÂ ofÂ accountabilityinternet-basedÂ fraudÂ perpetratorsin the decision Number Judges’ConsiderationsÂ inÂ makeÂ aÂ verdictÂ onÂ theÂ internet-basedÂ fraudcrimeÂ DecisionÂ NumberÂ 1791/2019Â /Â Pid.susÂ /Â PN.Sby. his study uses the data analysis method used in this study is a normative qualitativeÂ analysis method. The data collection method uses the library research method. This methodÂ usedÂ toÂ collectÂ secondaryÂ data,Â severalÂ instrumentstheÂ collection usedÂ isÂ literatureÂ study. based fraud in verdicts Number.1791 / 2019 /Â Pid.susÂ /Â PN.Sby.supportingÂ factorsÂ inÂ enforcement cardingÂ crime, namely witness statements, expert statements, evidence. The defendant wasÂ charged under Article 30 paragraph (2) in conjunction with Article 46 paragraph (2) RI LawÂ No. 19 of 2016 concerning amendments to Law of the Republic of Indonesia No. 11 of 2008Â regarding Information and Electronic Transactions, Article 30 paragraph (2) in conjunctionÂ with Article 46 paragraph (2) RI Law No. 19 of 2016 concerning amendments to Law of theÂ Republic of Indonesia No. 11 of 2008 regarding Information and Electronic Transactions inÂ conjunctionÂ withÂ ArticleÂ 56Â paragraphÂ (2)oftheÂ CriminalÂ CodeÂ andÂ Law NumberÂ 8Â ofÂ 1981. Â Judges’Â LegalÂ ConsiderationsÂ inÂ applyingÂ criminalprovisionsÂ againstÂ theÂ criminalÂ perpetrator in the case of decision Number.1791/2019 /Â Pid.susÂ /Â PN.Sby, The defendant wasÂ sentencedÂ byÂ the Panel of JudgesÂ respectivelyÂ for the Defendant 1Â 5 (five)Â monthsÂ andÂ 15Â (fifteen) days and a fine of Rp.3,000,000 (three million rupiah) and for Defendant II for 6 (six)Â months and 15 (sixteen) days and a fine of IDR 3,000,000 (three million rupiah). Because it hasÂ been legally proven to have committed a carding crime as regulated in the Law on InformationÂ andÂ ElectronicÂ Transactions.